SEMIOTIKA IKLAN “KEKHAWATIRAN”: SOLUSI KELUAR DARI MASALAH KEHIDUPAN - Hasyim, Muhammad (Universitas Hasanuddin, 2014)
Often people buy a product just worried. Fearing that the bone loss at a young age (especially women), people consume high-calcium milk; for fear of body fat because fat accumulates, then people buy milk diet, slimming tea (tea sleaming), etc. On the basis of this phenomenon, thispaper aims to analyze the construction of the meaning of 'concern' at the commercial products into advertising media. 'Concern' is seen as a sign, which is represented in the verbal and nonverbal language (video), which are then transferred into the meaning of concern commercialadvertisements.This paper uses a review of semiotics as a method to analyze the meaning of a concern as thereality of the sign. The results showed that the meaning of concern made by advertisers ispersuasive way to lead consumers to use the product being promoted, so that the function ofadvertising done by the manufacturer does not emphasize on functionality or usability of theproduct but a social function (concerns). Television advertising medium utilizing humanweaknesses, by selling a